Servitudes in Byzantine and Serbian medieval law - Šarkić Srđan (Zbornik Radova Vizantološkog Instituta, 2013)
In the first part of the work we find the Roman concept of servitudes, and then the rules on servitudes taken from Roman law to Byzantine and Serbian mediaeval law. Serbian legal sources knew the following rustic servitudes: rights of way, rights of pasture, rights to water and watering one’s cattle. Among the personal servitudes we find ususfructus and usus.